Peran Logo Sebagai Simbol Identitas, Kreativitas, dan Penunjang Online Marketing UMKM Batik Mangklek - Andreas Tigor Oktaga; Prihati Prihati; Aji Priyambodo; Kristiawan Nurdianto; Martinus Apun Heses (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Batik Mangklek MSME, located in Margosari Village, Kendal Regency, faces challenges in strengthening its visual identity and branding. These MSMEs need a logo design as a symbol of identity that can increase the attractiveness and differentiate the products in the market, especially in supporting online marketing. The objective of this activity is to design a logo that represents the cultural values and creativity of Batik Mangklek, which is expected to support their digital marketing strategy. The logo creation process involved surveys, interviews, and research on design trends and logo philosophies that match the characteristics of local batik. As a result, the logo successfully combines elements of local culture and creativity, with a philosophy that reflects the character of Batik Mangklek. The logo was handed over to Batik Mangklek MSMEs, along with usage guidelines on online promotional media and product packaging. In conclusion, the creation of this logo has a positive impact on strengthening the visual identity of Batik Mangklek MSMEs and increasing the effectiveness of digital marketing strategies, so that their products are more easily recognized and demanded by consumers.